EXTH-62. TG02, A NOVEL TARGETING OF TRANSCRIPTION AND METABOLISM IN GLIOBLASTOMA. (6th November 2017) - Su, Yu-Ting; Chen, Robert; Song, Hua; Zhang, Qi; Li, Aiguo; Celiku, Orieta; Meetze, Kristan; Estok, Tom; Maric, Dragan; Zhuang, Zhengping; Yang, Chunzhang; Zhang, Wei; et al.
Abstract: BACKGROUND: Glioblastoma (GBM), a common malignant brain tumor, is highly resistant to most treatments, largely due to disease heterogeneity and resistance mechanisms. We investigated TG02, a multi-kinase inhibitor with established anti-tumor activities in hematologic malignancies, for a potential GBM therapy. We previously demonstrated that TG02 inhibited CDK9-mediated transcriptional regulation of anti-apoptotic proteins and induced Cytochrome c release, inducing cell apoptosis through Caspase-3 activation. Additionally, TG02 and Temozolomide (TMZ) demonstrated a synergistic anti-glioma effect in vivo and in vitro . METHODS: A phosphorylation mimic form of CDK9 was overexpressed in GBM cell and cell viability was via cell counting. NADH dehydrogenase activity was measured to determine mitochondrial respiratory chain complex I activity. The glycolytic effects were measured by Seahorse assay and Western blotting of the key enzymes. Mitochondrial membrane potential change and apoptosis were measured by FACS with DiOC6, and Hoechst/PI staining, respectively. Pharmacodynamic studies were carried out using a syngeneic GBM mouse model. RESULTS: We demonstrated that overexpressed phosphorylation mimic form of CDK9 partially blocked TG02-induced cell death, suggesting that CDK9 mediates TG02-induced cytotoxicity. We demonstrated that TG02 caused mitochondrial dysfunction partially by reducing mitochondrial respiratory chain complex I activity. Additionally, TG02 inhibited glycolysis by downregulating key glycolytic regulators, including Hexokinase-2 (HK-2) and Pyruvate kinase M2 (PKM2), leading to ATP depletion. Combined treatment further enhanced ATP depletion, explaining the synergism between TG02 and TMZ. More importantly, TG02 did not cause mitochondrial damage and apoptosis in normal human astrocytes, suggesting a feasible therapeutic window for TG02. Furthermore, our pharmacodynamic studies confirmed that TG02 suppressed CDK9 activity in brain tumor tissues. CONCLUSIONS: TG02 has unique anti-glioma effects through transcriptional regulation of survival proteins, and reduction of cellular energy level in GBM cells. Our preclinical results have led to an ongoing Phase I//II clinical trial for patients with refractory GBM (NCT02942264).